Pengolahan Limbah Cair Pembuatan Minuman Ringan Dengan Reaktor Semiaerobik, TCPS, Reaktor Anaerobic Dua Tahap - Suprihatin, Hasti (Universitas Riau, 2018)
The existing soft drink factory can produce liquid organic waste with a COD content starts from 6,000 mg/l to 15,000 mg/l with a discharge by 10 m3/day to 100 m3/day. The objective of the research is to obtain organic waste processing equipment that produces processing that meets the threshold value. The research outcomes are as a reference for the industry that requires a representative organic waste treatment unit.The research is divided into two stages in two years. The first year of the research is semi-aerobic and anaerobic process, then for second year is aerobic process research, semi-aerobic process, anaerobic process and aerobic process. The 12 hours HRT process at the first run resulted in a COD concentration of 12,000 mg/l to 8,765 mg/l directly entering an anaerobic I and out 4,640 mg/l and entering anaerobic II reactor and exiting with COD 1,380 mg/l. Decrease percentage of total COD (12,000 – 1,380) x 100 /12,000 = 88.5%. The 18 hours HRT process at the first run resulted in a COD concentration by 12,000 mg/l to 8,665 mg/l entering the anaerobic reactor I and out 4,125 mg/l and entering the anaerobic II and out with COD 965 mg/l. Decrease in total COD (12,000 - 965) x 100 / 12,000 = 91.95%.From the experimental stage of semi-aerobic step-screening-anaerobic treatment of two-stage liquid liquor soft drink obtained COD concentration of 12,000 mg/l can be reduced concentration to the threshold specified with removal of 88.5% - 91.95%.